The Correlation between Self-Regulated Learning and Motivation to The Achievement of PAI and Budi Pekerti at SMPN 2 Kediri - Qurrotul A'yun (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2017)
This research is the result of quantitative research with multiple correlation design, aiming to test the theory from D.H. Schunk and B.J. Zimmerman that Self-regulated learning is generally characterized as an active participant who efficiently controls their own learning experiences in different ways, and answers questions about how much self-regulated learning, motivation, and learning outcomes of PAI and Budi Pekerti of students SMPN 2 Kediri, and there is correlation between self-regulated learning and motivation to the learning outcomes of PAI and Budi pekerti at SMPN 2 Kediri. Data collection techniques in this study are documentation and questionnaires of self-regulated learning and motivation. While the analysis technique is kendall's tau. The results of this study show, first of all, that self-regulated learning is categorized as very high; second, motivation is categorized high; third, PAI and Budi Pekerti learning outcomes are categorized as high based on score criteria; fourth, there is a significant relationship between self-regulated learning and motivation to the learning outcomes of PAI and Budi Pekerti at SMPN 2 Kediri.